A NEW 92-K HIGH-T(C) SUPERCONDUCTOR - HG-CONTAINING TL-BASED 1212 PHASE - Liu, R; Hu, S; Jefferson, D; Edwards, P; Hunneyball, P (1993)
Bulk superconductivity up to 92 K has been achieved in the mercury-containing curprate (Tl0.5Hg0.5)Sr2(Ca1-xYx)Cu2 O7-δ when x=0.3. Based on X-ray and electron diffraction and electron probe microanalyzer results, we identify the phase responsible for the superconductivity to be similar to that of (Tl0.5Pb0.5)Sr2CaCu2O7 (so-called 1212 phase) with a space group of P4/mmm and lattice constants of a ∼ 3.8 Å and c ∼ 12.0 Å. Moreover, neither superlattice nor intergrowth along the a* and c * directions were observed by electron diffraction. An increase in Ca2+ doping, 0.5≤x≤0.3, into the Y3+ sites results in a maximum superconducting transition temperature (Tc) at around 92 K for x=0.3. For compositions x<0.3, a decrease in Tc was observed. © 1993.